The p53 activation domain binds the TATA box-binding polypeptide in Holo-TFIID, and a neighboring p53 domain inhibits transcription. - Liu, X (1993)
Antioncogene product p53 is a transcriptional transactivator. To investigate how p53 stimulates transcription, we examined the interaction of p53 with general transcription factors in vitro. We found that p53 binds directly to the human TATA box-binding polypeptide (TBP). We also observed a direct interaction between p53 and purified holo-TFIID, a complex composed of TBP and a group of TBP-associated polypeptides known as TAFs. The p53 binding domain on TBP was mapped to the conserved region of TBP, including residues 220 to 271. The TBP binding domain on p53 was mapped to the p53 activation domain between residues 20 and 57. To analyze the significance of the p53-TBP interaction in p53 transactivation, we compared the ability of Gal4-p53 fusion proteins to bind to TBP in vitro and to activate transcription in transient transfection assays. Fusion proteins which bound to TBP activated transcription, and those that did not bind to TBP did not activate transcription to a detectable level, suggesting that a direct interaction between TBP and p53 is required for p53 transactivation. We also found that inclusion of residues 93 to 160 of p53 in a Gal4-p53 fusion repressed transcriptional activation 100-fold. Consequently, this region of p53 inhibits transcriptional activation by the minimal p53 activation domain. Highest levels of activation were observed with sequences 1 to 92 of p53 fused to Gal4, even though this construct bound to TBP in vitro with an affinity similar to that of other Gal4-p53 fusion proteins. We conclude that TBP binding is necessary for p53 transcriptional activation and that p53 sequences outside the TBP binding domain modulate the level of activation.